Life expectancy inequalities between regions of China 2004–2020: contribution of age- and cause-specific mortality - Zhang, Leyi; Sun, Lijuan (Frontiers in Public Health, 2023)
China's rapid development since the early 2000s has impacted its epidemiological transition, potentially causing health disparities across regions. This study uses Life Expectancy (LE) to assess health trends in China's eastern, central, and western regions, examining LE gains relative to empirical trends and investigating age and causes of death mortality contributing to regional gaps. Utilizing a log-quadratic model and data from 2004 to 2020, the study estimates LE in China and its regions using census and death cause surveillance data. Employing the HMD and the LE gains by LE level approach, it analyzes China's LE gains compared to developed countries. The study investigates changes in LE gaps due to age and causes of death mortality improvements during 2004-2012 and 2012-2020 through the LE factor decomposition method. Results show China's LE grew faster than developed countries from 2000 to 2020, with men's growth aligning gradually with empirical trends, and women experiencing slightly higher growth rates. Regional LE disparities significantly reduced from 2004 to 2012, with a marginal reduction from 2012 to 2020. Changing LE gaps align with expected trends in developed countries, with cardiovascular diseases and malignant neoplasms contributing to expanding regional gaps, while neurological disorders and diabetes play a more negative role. Despite consistent reductions, recent years show a slower pace in decreasing LE disparities in China. To address this, targeted efforts should improve mortality rates related to cardiovascular diseases, neoplasms, neurological disorders, and diabetes, particularly in the western region, prioritizing equal access to basic public health services nationwide.